Education of Young People with Impaired Psychophysical Development as a Condition for Their Integration into Society - Arkhypova, Svitlana; Smerechak, Lesya (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
The article deals with the role of social institutions in the development of the educational needs of young people with disabilities. The current theoretical research and practical aspects of work with young people with special educational needs in terms of university education are analyzed. It is proved that the system of higher education for young people with defects of psychophysical development should adjust to the content and process of learning in such a direction: usage the existing legal framework and its further improvement in order to stimulate the development of the system of education of young people with defects of psychophysical development; creating organizational and pedagogical conditions to regulate the process of learning beginning with diagnostic support, training, correction as well as certain educational outcomes at a particular stage and the prognosis for the future; setting norms of workload in the curriculum and educational plans should be determined taking into account the age and health of young people; adaptation of means, methods and technologies of training with the regard to the nature of deprivation of a young person and activation of compensatory and developmental mechanisms and focus on self-development, self-education and self-improvement.